2011
DOI: 10.1108/01435121111112916
|View full text |Cite
|
Sign up to set email alerts
|

Employability skills of LIS graduates in Pakistan: needs and expectations

Abstract: Purpose -This paper aims to analyze the opinion of young and senior library and information science (LIS) professionals in Pakistan on LIS curricula and its relevance to market needs to enhance employability. Design/methodology/approach -A mixed research method was used to collect data from professionals through two questionnaires, focus group and personal experiences. Findings -The findings reveal that the LIS curriculum offered at the University of the Punjab (PU) is up to date and well designed but it is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The generic skills [12][13][14] are not only the ability of initial employment, but also the potential development. In general, employers now pay more and more attention to the employability and employability skills of the staffs [15][16][17][18][19][20][21]. How to know and understand the employability skills which the employers value [11][12][13][14] is now being an important issue which the education sectors need to confront with.…”
Section: Introductionmentioning
confidence: 99%
“…The generic skills [12][13][14] are not only the ability of initial employment, but also the potential development. In general, employers now pay more and more attention to the employability and employability skills of the staffs [15][16][17][18][19][20][21]. How to know and understand the employability skills which the employers value [11][12][13][14] is now being an important issue which the education sectors need to confront with.…”
Section: Introductionmentioning
confidence: 99%
“…The study provides an overview of the di culties library and information science (LIS) education and the reasons why employers and professionals in the eld are dissatis ed. The study's results may assist not only LIS educators but other elds such as management, marketing and tourism related spheres in developing and designing necessary skills (Ameen & Warraich, 2011).…”
Section: Literature Reviewmentioning
confidence: 93%
“…WIUT LRC has a lot of activities, workshops, training and blended mode courses which can enhance the students' transferable skills that can assist in their employability. Ameen & Warraich (2011) describe employability as required skills for getting the job and doing it professionally. They can be taught based on academic and thinking skills and individual qualities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies conducted by several researchers have outlined a number of employability skills (e.g. Mgaiwa, 2021; Pradhan, 2015; Warraich and Ameen, 2019). In particular, these studies have identified presentation skills, problem-solving aptitude, report-writing skills, online-searching skills, customer service skills, a positive attitude, time-management capability, teaching skills, learning skills, planning skills and organizational skills as important in the job market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally, LIS schools are adapting their curricula to the technological and socio-economic changes taking place. For example, in addition to revising and revitalizing their curricula, some schools are increasing their collaboration with other academic departments to enhance the customizability of their academic programmes (Ismail and Khan, 2021; Warraich and Ameen, 2019). Likewise, schools have changed their names, practices and courses offered (Buarki et al, 2011).…”
Section: Introductionmentioning
confidence: 99%